Classification and characterization of Japanese consumers' beef preferences by external preference mapping. (23rd February 2017) - Sasaki, Keisuke; Ooi, Motoki; Nagura, Naoto; Motoyama, Michiyo; Narita, Takumi; Oe, Mika; Nakajima, Ikuyo; Hagi, Tatsuro; Ojima, Koichi; Kobayashi, Miho; Nomura, Masaru; Muroya, Susumu; et al.
Abstract: BACKGROUND: Over the past few decades, beef producers in Japan have improved marbling in their beef products. It was recently reported that marbling is not well correlated with palatability as rated by Japanese consumers. This study sought to identify the consumer segments in Japan that prefer sensory characteristics of beef other than high marbling. RESULTS: Three Wagyu beef, one Holstein beef and two lean imported beef longissimus samples were subjected to a descriptive sensory test, physicochemical analysis and a consumer ( n = 307) preference test. According to consumer classification and external preference mapping, four consumer segments were identified as 'gradual high‐fat likers', 'moderate‐fat and distinctive taste likers', 'Wagyu likers' and 'distinctive texture likers'. Although the major trend of Japanese consumers' beef preference was 'marbling liking', 16.9% of the consumers preferred beef samples that had moderate marbling and distinctive taste. The consumers' attitudes expressed in a questionnaire survey were in good agreement with the preference for marbling among the 'moderate‐fat and distinctive taste likers'. CONCLUSION: These results indicate that moderately marbled beef is a potent category in the Japanese beef market. © 2017 Society of Chemical Industry